Implementation of the Tallaqi, Tafahhum, Tikrar and Murajaah (3T+1M) Method in the Tahfidz Istana Palace Learning Program - Ulumiyah, Miftakhul; Maarif, Muhammad Anas; M. Afif Zamroni (Program Pascasarjana Universitas Ibrahimy, 2021)
This article aims to discuss the implementation of the Tallaqi, Tafahhum, Tikrar and Murajaah (3T + 1M) method in learning the Tahfidz Palace at MA Miftahul Hikmah Jambuwok Trowulan Mojokerto. The type of research used in this article is qualitative with a case study approach. While the validity of the data using the triangulation technique. The result of this article is the implementation of the 3T + 1M method in the tahfidz palace learning program divided into three stages, 1) preparation in the form of conducting supervisor qualifications, determining memorization time, determining memorization methods, grouping classes, determining memorization targets, prepare daily programs and prepare mentally for tahfidz program participants, 2) implementation is carried out by applying the 3T + 1M method and 3) evaluation by means of daily evaluations, mid-semester evaluations, end-of-semester evaluations, end of school year evaluations (acquisition tests), examinations for each acquisition 5 juz (terminal exam), remedial and graduation. Meanwhile, the inhibiting factors for the implementation of the 3T+1M method in the Tahfid Palace learning program are the tahfidz program which is still running, the lack of supervisors, fatigue faced by students, and different levels of student intelligence.